Pengaruh Berita Hoax di Indonesia Menurut Pandangan Mahasiswa Teknik Lingkungan Kelas B Angkatan 2022 UPN "Veteran" Jawa Timur - Kinanti R. Hayati; Anindya Loviantary; Deswina Amalia Iswandy (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Hoaxes have become an issue that increasingly worries society because of their potential negative impact on social stability, security and public trust. Therefore, it is important to understand the views of students as young people who play an important role in building a better future for Indonesia. This study aims to investigate the views of Class B Environmental Engineering students class of 2022 UPN "Veteran" East Java regarding the influence of hoax news in Indonesia. The research method used is quantitative by using a questionnaire as a data collection instrument. The sample for this research was Environmental Engineering students class B class of 2022 at UPN "Veteran" East Java. The data collected will be analyzed using descriptive statistical methods and factor analysis. The results of this study indicate that the majority of Class B Environmental Engineering students class of 2022 at UPN "Veteran" East Java have a fairly good understanding of hoax news and its influence in Indonesia. However, this study also found that there were still a small number of students who were unable to distinguish between hoax news and factual news. Several respondents admitted that they were sometimes influenced by hoax news and were less critical in consuming the information they received. This shows the need to increase media literacy and be critical in filtering the information received. In conclusion, the influence of hoax news in Indonesia has had a significant impact on society, including Class B Environmental Engineering students class of 2022 UPN "Veteran" East Java. Awareness about hoax news and the ability to distinguish between factual and hoax news is very important to face the increasingly complex information challenges in this digital era.Â